A review of the management of prelabor rupture of membranes (PROM) more than 36-week gestation. (16th November 2010) - Fatima, F; Mathur, M; Shetty, A
Abstract : Approximately 8% of women have term Prelabor rupture of membranes (PROM). Over 60% of these women labour spontaneously within 24 h and over 95% within 72 h following PROM. As the time interval between PROM and the onset of labour increases, so may the risk of maternal and fetal infection. In this small cohort study of 100 women with term SROM 40% laboured spontaneously within 24–48 h of PROM. Among this group, 34 women laboured within 24 h of PROM, while the remaining six laboured within 36 h. In the spontaneous labouring women, syntocinon augmentation for slow progress was indicated in 18%. Mode of delivery in these 40 women was vaginal in 67% and a LSCS (lower segment Caesarean section) in 33%. Labour was induced in 57 % (n=57), of whom 29 women (51%) underwent induction of labour within 24 h of the PROM for indications including meconium stained liquor, maternal fever, suboptimal CTG and history of Group B streptococci. Mode of delivery in these 57 women was by vaginal route in 74%, while 26% were delivered by a Caesarean section. In total seven babies required admission to the neonatal unit, of whom three had neonatal sepsis. Of these seven, labour was induced in one for meconium stained liquor and in four for prolonged PROM, while two laboured spontaneously. This study shows outcomes including mode of delivery were not significantly different in those labouring spontaneously following PROM over 36 weeks gestation, and those who required induction.